Durability of rubberized asphalt binders containing waste cooking oil under thermal and ultraviolet aging. (13th September 2021) - Lyu, Lei; Pei, Jianzhong; Hu, Dongliang; Fini, Elham H.
Graphical abstract: Highlights: Bio-modification significantly enhances aging resistance of rubberized asphalt binder. Evolution of rubberized asphalt binders under thermal and UV aging were compared. The resistance against ultraviolet radiation is more notable than thermal aging. Enhancement of aging resistance was evidenced in lower sulfoxide and carbonyl formation. Abstract: Thermal oxidation and ultraviolet exposure contribute to major changes in the physicochemical and rheological properties of asphalt binder, leading to the deterioration of pavements. This paper investigates the merits of grafting bio-derived molecules onto particles of crumb rubber to create bio-modified rubberized asphalt binder with enhanced resistance to thermal aging and ultraviolet aging. The bio-modification of the crumb rubber was made via a hybrid process where molecules of waste cooking oil were grafted to rubber with the help of microwave radiation. The evolution of bio-modified rubberized asphalt during thermal aging and ultraviolet aging was then characterized and compared with those of conventional rubberized asphalt. Study results showed bio-modification was effective to delay both thermal aging and ultraviolet aging. However, the effectiveness varied with the type of aging with the resistance to thermal aging being enhanced by 35%-84% and the resistance to ultraviolet aging being enhanced by 34–106%. Overall, the synergy between waste cooking oil, crumb rubber, and asphalt binder led to a significant improvement in the resistance against aging, thereby promoting sustainability in construction while making use of two waste streams including waste cooking oil and crumb rubber from scrap tire.